2018
DOI: 10.1515/gps-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rare-earth metal on the zinc oxide nanostructures: application in the photocatalytic degradation of methylene blue and p-nitro phenol

Abstract: Rare-earth cerium (Ce)-doped zinc oxide (ZnO) spherical nanoparticles were synthesized by using the co-precipitation method. The doped materials were characterized by means of the X-ray diffraction, Williamson-Hall Plot, and field emission scanning electron microscopy analyses. The prepared nanoparticles exhibit a hexagonal wurtzite structure as observed from the XRD measurements. Energy dispersive X-ray spectroscopy data confirmed the purity of the prepared samples. The photocatalytic activity of the rare-ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Other peaks were observed corresponding to the degraded products of the dye. The peaks obtained at m / z 319, 303, 279, 269, 216, 192 and 135 were attributed to the fragmented ions which were fully matched with earlier reports . In addition to these peaks, numerous peaks of insignificant intensity were also present in the spectrum (Figure b) which indicated that most of the MB molecules have been mineralized.…”
Section: Resultssupporting
confidence: 88%
“…Other peaks were observed corresponding to the degraded products of the dye. The peaks obtained at m / z 319, 303, 279, 269, 216, 192 and 135 were attributed to the fragmented ions which were fully matched with earlier reports . In addition to these peaks, numerous peaks of insignificant intensity were also present in the spectrum (Figure b) which indicated that most of the MB molecules have been mineralized.…”
Section: Resultssupporting
confidence: 88%
“…The active species, including OH•, O2-• and h + react in situ with MB to form certain intermediate compounds as proposed by other reported results [32]. Furthermore, some possible intermediates such as N,N-dimethyl-paraphenylenediamine and 1,2,4-trihydroxybenzene were identified when MB was attacked by OH•, O2-• and h + species [33], and subsequently converted to carbon dioxides and water by ring opening reactions.…”
Section: 3%mentioning
confidence: 52%
“…4. The molecular ion peak at m / z of 284 confirmed the existence of the MB molecule 34. The m / z peaks of mass spectra at 270 (one methyl group left) and 256 (two methyl groups left) corresponded to the ratios of m / z of the demethylation.…”
Section: Resultsmentioning
confidence: 77%